2019
DOI: 10.1139/cjps-2018-0189
|View full text |Cite
|
Sign up to set email alerts
|

Development of pre-breeding diploid potato germplasm displaying wide phenotypic variations as induced by ethyl methane sulfonate mutagenesis

Abstract: Mutations are the key drivers for evolution and diversification in plants. In varietal selection, sources for variation are always sought as starting breeding materials. Thus, in the absence of desired natural variations in breeding populations, targeted or random mutagenesis is applied to induce variations. Cultivated potato (Solanum tuberosum L.) is autotetraploid crop species with a narrow and highly heterozygous genetic base, and the complexity of its genome makes its genetic studies more difficult. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Using SNP polymorphism data derived from seven genes involved in bittering acid production (Paniego et al 1999;Clark et al 2013;Li et al 2015), the current study revealed a large variation (natural and EMS-induced) in hop seedlings, true hop seeds, and mutagenized explant clones derived from Alpharoma. Similar EMS-induced SNP variations have been reported in flax, potato, tomato, and eggplants (Muth et al 2008 Chantreau et al 2013;Shikata et al 2015;Fofana et al 2017;Xiou et al 2017;Somalraju et al 2018). By challenging wild and EMS-treated clones with DM, a diversity in disease response was observed in both types, suggesting that wild feral types had persisted and co-evolved in the environment with epiphytotic DM epidemics and might have developed adaptation mechanisms through natural mutations during the nearly 200 years of co-evolution with different local DM strains.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Using SNP polymorphism data derived from seven genes involved in bittering acid production (Paniego et al 1999;Clark et al 2013;Li et al 2015), the current study revealed a large variation (natural and EMS-induced) in hop seedlings, true hop seeds, and mutagenized explant clones derived from Alpharoma. Similar EMS-induced SNP variations have been reported in flax, potato, tomato, and eggplants (Muth et al 2008 Chantreau et al 2013;Shikata et al 2015;Fofana et al 2017;Xiou et al 2017;Somalraju et al 2018). By challenging wild and EMS-treated clones with DM, a diversity in disease response was observed in both types, suggesting that wild feral types had persisted and co-evolved in the environment with epiphytotic DM epidemics and might have developed adaptation mechanisms through natural mutations during the nearly 200 years of co-evolution with different local DM strains.…”
Section: Discussionsupporting
confidence: 71%
“…Using Alpharoma as starting material, internodes were collected from in vitro plants and treated with different concentrations (0.25%, 0.5%, or 1% (v/v)) of EMS diluted in sterile water for 1 or 3 h. The treated internodes were rinsed five times with water as described by Somalraju et al (2018). The explants were incubated in callus induction media (Batista et al 2000) and plants were regenerated (Roy et al 2001).…”
Section: Ems Mutagenesis Of Alpharomamentioning
confidence: 99%
See 2 more Smart Citations
“…The plant materials used in this study consisted of four potato genotypes including two registered varieties ('Superior' and 'Russian Blue') and two EMSmutagenized diploid potato lines ('EMS5-512ʹ and 'EMS4-901ʹ) derived from a diploid EMS-mutagenized potato genetic resource (Somalraju et al 2018). 'Superior' and 'Russian Blue' cultivars have contrasting tuber skin and flesh colours.…”
Section: Plant Materialsmentioning
confidence: 99%